Pengaruh Marketing Mix (4P) Terhadap Keputusan Pembelian Dimediasi Kepuasan Konsumen Pada Usaha UMKM - Achmad Dzikrulloh; Abid Muhtarom; Moh Muklis Sulaeman; Moh Heru Budi Santoso (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Micro, Small and Medium Enterprises (MSMEs) are businesses that have an important role in the Indonesian economy, both in terms of the jobs created and in terms of the number of businesses. One of them is the SME welding workshop located in Dermolemahbang Village, Sarirejo District, Lamongan Regency, namely UD. Bakri Welding Workshop is a welding workshop that produces rice planting equipment in Dermolemahbang Village, Sarirejo District, Lamongan Regency. UD. Bakri Welding Workshop is a welding workshop business that has been established since 2010. The products produced by UD. Welding Bakri is a rice planting tool, which is a tool for planting rice seeds, this tool is very easy to use, and also more durable compared to rice planting equipment products sold in the market, because this tool is made of iron and tools made in the market are still using plastic. This research method uses quantitative methods using a Likert scale and the population used or taken is all consumers from UD. Las Bakri Lamongan, with a sample of 130 respondents. And by using the SEM research analysis method with the Smart-PLS version 3.2.7. The tests used in this study are the outer model test, mediation test and hypotheses.